Demand response evaluation of RIES based on improved matter-element extension model. (1st December 2020) - Wang, Yongli; Li, Fang; Yang, Jiale; Zhou, Minhan; Song, Fuhao; Zhang, Danyang; Xue, Lu; Zhu, Jinrong
Abstract: With the revolution of traditional economic and social patterns based on concentrated fossil energy intensive consumption, regional integrated energy systems (RIES) have gradually become an important trend for future energy consumption. As an important technical means of integrated energy demand side management, demand response helps to improve the smooth and reliable operation of the integrated energy system (IES). Meanwhile, it is of great significance to improve national energy security and the environment. This paper focuses on the demand response evaluation of RIES based on improved matter-element extension model. Firstly, with the introduction of the RIES demand response evaluation mechanism, the demand response index system of RIES is established from five dimensions: user load, user energy usage, user energy reliability, user energy consumption, and user energy habits. Based on the demand response evaluation index system, the potential demand response users of the integrated energy system are graded into four levels: rewarded user (I), encouraged user (II), general user (III), and non-encouraged user (IV).Secondly, based on the analytic hierarchy process and entropy method to obtain more accurate comprehensive weights, the RIES demand response evaluation model is established by the matter-element extension method. Finally, in order to illustrate the advantages of this method, 10 objects were selected from the regional integrated energy systems demand response project of a Chinese city for evaluation and analysis. The results show that the demand response abilities of the 10 evaluation objects are all at level I, indicating that the automatic demand response (ADR) of 10 evaluation objects is good. Highlights: From the user side, an index system for RIES demand response evaluation is proposed. The evaluation standard of the demand response evaluation index system in RIES was proposed. An improved matter-element extension demand response assessment model of RIES is established. The demand response grade of the system could be realized.